1989
DOI: 10.1111/j.1365-2796.1989.tb01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Rectal potential differences in irritable bowel syndrome and in inflammatory bowel diseases in man

Abstract: We have studied rectal potential difference (pd) in 200 subjects: 30 healthy volunteers or control patients, 46 patients with irritable bowel syndrome (IBS) and painless diarrhoea (group I), 60 IBS patients without diarrhoea (group II) and 64 patients with inflammatory bowel disease (IBD) with (group III, n = 41) or without (group IV, n = 23) rectal involvement. Pd measurement used a rectal perfused probe and a subcutaneous needle both connected, via agar-KCl bridges, to calomel electrodes and a millivoltmeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
3
0
2
Order By: Relevance
“…Interestingly, IgE‐induced responses in Isc were attenuated in previously infected animals. This, together with the increased tonic activity of MMCs, might suggest the presence of desensitization mechanisms to MMC mediators, as previously described in patients of gastrointestinal disorders associated with mastocitosis 21 . Alternatively, reduced secretory responses to MMC mediators, together with the alterations in epithelial and neural responses discussed previously, might represent the interplay of feedback regulatory mechanisms aiming to minimize a state of continuous epithelial overstimulation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Interestingly, IgE‐induced responses in Isc were attenuated in previously infected animals. This, together with the increased tonic activity of MMCs, might suggest the presence of desensitization mechanisms to MMC mediators, as previously described in patients of gastrointestinal disorders associated with mastocitosis 21 . Alternatively, reduced secretory responses to MMC mediators, together with the alterations in epithelial and neural responses discussed previously, might represent the interplay of feedback regulatory mechanisms aiming to minimize a state of continuous epithelial overstimulation.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, Ussing chamber studies performed to evaluate this postinfectious phase demonstrated EBF disruptions which resemble to a certain extent findings in patients with functional gastrointestinal disorders 20–23 . In particular, alterations in electrical conductance and passage of fluorescent tracers revealed a significant jejunal permeability defect during the postinfectious phase in the rat.…”
Section: Discussionmentioning
confidence: 52%
“…Even though until now, no correlation has been established between fecal level of serine‐protease activity and the intensity/frequency of symptoms, it is tempting to speculate, based on animal data, that such activity contributes to the genesis of symptoms and particularly abdominal pain in these patients. Interestingly, a decreased colonic potential difference, corresponding to an increase in permeability, has been found in IBS‐D 49 and UC 50 patients compared with healthy subjects. We can speculate that this decreased potential difference is linked to the elevated protease activity found in these patients through an activation of PAR‐2.…”
Section: Luminal Proteases Par‐2 and Ibsmentioning
confidence: 95%
“…The importance of the colon in relation to bowel habits is illustrated by the fact that constipation occasionally occurs also in patients with celiac disease. 24 A concomitant disturbance in colonic mucosal function may indeed occur in d-IBS, as Pienkowski et al 33 have shown that a group of d-IBS patients had a decreased colonic PD compared with controls, a pattern similar to that in ulcerative colitis, 34,35 although of lower magnitude. When interpreting the current data, one should regard the motility-related PD signal as a marker for submucous plexus activity at the measuring site only.…”
Section: Discussionmentioning
confidence: 99%